JMJD8 is a novel endoplasmic reticulum protein with a JmjC domain - Yeo, K.S.; Tan, M.C.; Lim, Y.Y.; Ea, C.K. (Nature Publishing Group, 2017)
Jumonji C (JmjC) domain-containing proteins have been shown to regulate cellular processes by hydroxylating or demethylating histone and non-histone targets. JMJD8 belongs to the JmjC domain-only family that was recently shown to be involved in angiogenesis and TNF-induced NF-κB signaling. Here, we employed bioinformatic analysis and immunofluorescence microscopy to examine the physiological properties of JMJD8. We demonstrated that JMJD8 localizes to the lumen of endoplasmic reticulum and that JMJD8 forms dimers or oligomers in vivo. Furthermore, we identified potential JMJD8-interacting proteins that are known to regulate protein complex assembly and protein folding. Taken together, this work demonstrates that JMJD8 is the first JmjC domain-containing protein found in the lumen of the endoplasmic reticulum that may function in protein complex assembly and protein folding.